Characterization of Complementary and Alternative Medicine-Related Consultations in an Academic Drug Information Service. (December 2016) - Gregory, Philip J.; Jalloh, Mohamed A.; Abe, Andrew M.; Hu, James; Hein, Darren J.
Purpose: To characterize requests received through an academic drug information consultation service related to complementary and alternative medicines. Methods: A retrospective review and descriptive analysis of drug information consultations was conducted. Results: A total of 195 consultations related to complementary and alternative medicine were evaluated. All consultation requests involved questions about dietary supplements. The most common request types were related to safety and tolerability (39%), effectiveness (38%), and therapeutic use (34%). Sixty-eight percent of the requests were from pharmacists. The most frequent consultation requests from pharmacists were questions related to drug interactions (37%), therapeutic use (37%), or stability/compatibility/storage (34%). Nearly 60% of complementary and alternative medicine-related consultation requests were able to be completely addressed using available resources. Among review sources, Natural Medicines Comprehensive Database, Clinical Pharmacology, Micromedex, and Pharmacist's Letter were the most common resources used to address consultations. Conclusion: Utilization of a drug information service may be a viable option for health care professionals to help answer a complementary and alternative medicine-related question. Additionally, pharmacists and other health care professionals may consider acquiring resources identified to consistently answering these questions.